2016
DOI: 10.1038/srep37553
|View full text |Cite
|
Sign up to set email alerts
|

Targeted killing of myofibroblasts by biosurfactant di-rhamnolipid suggests a therapy against scar formation

Abstract: Pathological myofibroblasts are often involved in skin scarring via generating contractile force and over-expressing collagen fibers, but no compound has been found to inhibit the myofibroblasts without showing severe toxicity to surrounding physiological cells. Here we report that di-rhamnolipid, a biosurfactant secreted by Pseudomonas aeruginosa, showed potent effects on scar therapy via a unique mechanism of targeted killing the myofibroblasts. In cell culture, the fibroblasts-derived myofibroblasts were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 34 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Fibroblasts are the major effector cells in wound healing (21). In the process of hypertrophic scar formation, fibroblasts typically exhibit excessive proliferation, enhanced migration and inhibited apoptosis, and secrete abundant extracellular matrix (22,23). It was previously identified that miRNA molecules serve important roles in the biological functions of hypertrophic scar fibroblasts, but their mechanisms of action requires further elucidation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are the major effector cells in wound healing (21). In the process of hypertrophic scar formation, fibroblasts typically exhibit excessive proliferation, enhanced migration and inhibited apoptosis, and secrete abundant extracellular matrix (22,23). It was previously identified that miRNA molecules serve important roles in the biological functions of hypertrophic scar fibroblasts, but their mechanisms of action requires further elucidation (24).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, RHA may provide a robust and effective treatment by directly targeting myofibroblasts with less toxicity to neighboring normal cells. Our recent finding that the RHA showed effective preventive function against the scar formation on rabbit ears could provide a support in verifying the specific function of RHA in potentially treating fibrotic organs.…”
Section: Resultsmentioning
confidence: 99%
“…43 After 72 h co-culture, the medium was discarded and the cells were incubated with calcein-AM/PI solution (3 μL AM and 3 μL PI in 3 mL PBS) for 20 min, and then washed three times in PBS before imaging under a fluorescence microscope (OLYMPUS I × 70). 44…”
Section: Methodsmentioning
confidence: 99%